Analysis of the Role of Industry, Investment, Quality of Human Resources and Realization of Regional Expenditure in Improving the Quality of Economic Growth in Southeast Sulawesi Province - Nur, Muh.; Kalsum, Ummy; Sabilalo, Mahmudin A.; Tambunan, Rince; Makkulau, Andi Runis (Journal of Posthumanism, 2025)
Quality economic growth is the main goal in regional development, because it not only emphasizes increasing GRDP figures, but also on equalizing development results and improving community welfare. This research investigates how industrial activity, investment levels, the skill and education of the workforce (human resources), and the execution of the regional budget influence the quality of economic growth in Southeast Sulawesi Province. Furthermore, it seeks to determine how these factors contribute to improved living standards for the region’s population. This research uses a quantitative descriptive method with the research area limited to six districts and two cities in Southeast Sulawesi Province, and uses secondary data from various official agencies for the period 2006 to 2015. Data analysis was carried out using an econometric approach through a panel data regression model using the Eviews 7 application, as well as testing the significance of the model through the F, t and R² tests. The study reveals that, collectively, investment, industrial activity, human resource quality, and regional budget execution positively and significantly impact the quality of economic growth in Southeast Sulawesi Province. However, when examined individually, only investment and regional expenditure show a statistically significant influence. The quality of economic growth has been proven to have a positive and significant effect on improving the welfare of the people in the region. Therefore, the recommended policy strategies include strengthening the basic economic sector, increasing capital expenditure, improving the quality of human resources, equal distribution of regional budget allocations, and developing a people-based creative economy.